Key paediatric messages from the 2018 European Respiratory Society International Congress. Issue 2 (29th April 2019) - Nenna, Raffaella; Hunt, Katie A.; Dassios, Theodore; Collins, Jennifer J.P.; Rottier, Robbert J.; Liu, Norrice M.; Rottier, Bart; Goutaki, Myrofora; Karadag, Bülent; Prayle, Andrew; Fernandes, Ricardo M.; Parisi, Giuseppe Fabio; et al.
In this article, the Group Chairs and early career members of the European Respiratory Society (ERS) Paediatric Assembly highlight some of the most interesting findings in the field of paediatrics which were presented at the 2018 international ERS Congress. The 2018 international #ERSCongress in Paris, France reflected the @ERSTalk's commitment to support the continuing professional and academic development of the 1500 members of the Paediatric Assembly. http://ow.ly/P2Ck50pDRy6